Galectin‐3 and incident cognitive impairment in REGARDS, a cohort of blacks and whites. Issue 1 (26th April 2018) - Venkatraman, Anand; Callas, Peter; McClure, Leslie A.; Unverzagt, Fred; Arora, Garima; Howard, Virginia; Wadley, Virginia G.; Cushman, Mary; Arora, Pankaj
Abstract: Introduction: The relationship between serum galectin‐3 and incident cognitive impairment was analyzed in the Reasons for Geographic and Racial Differences in Stroke study. Methods: Baseline galectin‐3 was measured in 455 cases of incident cognitive impairment and 546 controls. Galectin‐3 was divided into quartiles based on the weighted distribution in the control group, and the first quartile was the referent. Results: There was an increasing odds of cognitive impairment across quartiles of galectin‐3 (odds ratios, 1.00 [0.68–1.46], 1.45 [1.01–2.10], and 1.58 [1.10–2.27] relative to the quartile 1; P trend = .003) in an unadjusted model, which persisted after adjusting for age, sex, and race ( P = .004). Adjustment for cardiovascular risk factors greatly attenuated this association (odds ratios, 0.97 [0.60–1.57], 1.52 [0.94–2.46], and 1.27 [0.76–2.12]; P = .15). The association differed by diabetes status ( P interaction, .007). Among nondiabetics (293 cases, 411 controls), those with galectin‐3 in the fourth compared with first quartile had an odds ratio of 1.6 (0.95–2.99; P trend, .02). In diabetics, the odds ratio was 0.23 (0.04–1.33). Discussion: Serum galectin‐3 was associated with increased risk of incident cognitive impairment in a large cohort study of blacks and whites but only in nondiabetics.